Postoperative metastasis prediction based on portal vein circulating tumor cells detected by flow cytometry in periampullary or pancreatic cancer - Tao, Lianyuan (Cancer Manag Res, 2019)
PURPOSE: The aim of this study was to evaluate the value of flow cytometry (FCM) detection of portal vein circulating tumor cells (CTCs) in predicting postoperative metastasis. METHODS: Samples of portal venous blood and peripheral blood were collected from 39 patients during surgery, and CTCs were detected by FCM, with confirmation by laser confocal microscopy and single-cell sequencing. RESULTS: Among all patients, a portal EpCAM+CD45- percentage ≥24.5×10(−4) (P=0.06), peripheral EpCAM+CD45- count ≥97/5 mL (P=0.034), peripheral EpCAM+CD45- percentage ≥4.4×10(−4) (P=0.042), and CA242≥3.5 U/mL (P=0.027) were significant predictors of metastasis. Further analysis showed that the portal EpCAM+CD45- ratio ≥24.5×10(−4) is a predictor of metastasis (P=0.025) in pancreatic cancer after curative resection. CONCLUSION: CTCs detected by FCM in portal venous blood are of significant value for the prediction of postoperative metastasis in pancreatic or periampullary tumors.